The progress of protein synthesis factors eIFs, eEFs and eRFs in inflammatory bowel disease and colorectal cancer pathogenesis - Huang, Conggai; Zhao, Qi; Zhou, Xiaoqing; Huang, Ran; Duan, Yi; Haybaeck, Johannes; Yang, Zhihui (Frontiers in Oncology, 2022)
Colorectal diseases are threatening human health, especially inflammatory bowel disease (IBD) and colorectal cancer (CRC). IBD is a group of chronic, recurrent and incurable disease, which may affect the entire gastrointestinal tract, increasing the risk of CRC. Eukaryotic gene expression is a complicated process, which is mainly regulated at the level of gene transcription and mRNA translation. Protein translation in tissue is associated with a sequence of steps, including initiation, elongation, termination and recycling. Abnormal regulation of gene expression is the key to the pathogenesis of CRC. In the early stages of cancer, it is vital to identify new diagnostic and therapeutic targets and biomarkers. This review presented current knowledge on aberrant expression of eIFs, eEFs and eRFs in colorectal diseases. The current findings of protein synthesis on colorectal pathogenesis showed that eIFs, eEFs and eRFs may be potential targets for CRC treatment.